Effect Of Elementary Education on Children's Social Skills, Self-Esteem, And Overall Mental Health - K, Kavitha.; Poonam, Poonam; M. Lalitha, M. Lalitha; Nidhya, G. Sri; B. Srinivas, B. Srinivas; Kumar, Vinod (Journal of Neonatal Surgery, 2025)
Elementary education plays a pivotal role in shaping the psychological and social foundations of children. This paper examines how primary education impacts the development of social skills, self-esteem, and overall mental health among children. Using a multidisciplinary approach that integrates insights from educational psychology, developmental theory, and mental health research, this paper explores how classroom environments, teacher-student relationships, peer interactions, and curricular design contribute to children’s psychosocial development. Findings from existing literature suggest that positive educational experiences foster not only academic growth but also enhance interpersonal skills and emotional well-being. Conversely, negative experiences during these formative years can lead to issues such as social withdrawal, low self-esteem, and long-term mental health challenges. The paper concludes with recommendations for educators, policymakers, and mental health professionals to create supportive educational environments that nurture the holistic development of children.